From Welfare Assistance to Empowerment: Rethinking Poverty Alleviation Strategies in Rural Communities - Syarifuddin HM; Yusriadi Yusriadi; Ummul Khair Alwi; A Yudistira; Anita Heldayanti (Journal of Indonesian Scholars for Social Research, 2026)
Poverty alleviation in rural communities is increasingly understood as a multidimensional development agenda that requires both social protection and community empowerment. This article aims to rethink poverty alleviation strategies by emphasizing the transformative potential of empowerment-based approaches in strengthening rural livelihoods and community resilience. Using a secondary data-based qualitative approach, this study analyzes relevant literature, statistical reports, and previous empirical studies on rural poverty reduction and community development. The article argues that sustainable poverty alleviation can be advanced by strengthening local capacity, expanding community participation, diversifying livelihoods, and improving access to education, health services, productive assets, and economic opportunities. Rural communities possess valuable social capital, local knowledge, mutual support systems, and adaptive livelihood practices that can serve as important foundations for inclusive development. Therefore, empowerment-based strategies should position rural communities not only as beneficiaries of development programs, but also as active partners in identifying opportunities, mobilizing local resources, and developing sustainable solutions. The article emphasizes the importance of collaborative governance involving government institutions, local leaders, community groups, civil society, and the private sector. Such collaboration can enhance the effectiveness of poverty alleviation by aligning formal development support with community-based initiatives. The article concludes that an empowerment-oriented model offers a promising pathway for rural poverty reduction because it promotes self-reliance, strengthens social resilience, and supports long-term socioeconomic transformation.